The Impact of the Loss of a Father's Role on a Daughter's Relationship Life - Sari, Novita (Educational Psychology Journal, 2025)
This study explores how the absence of a father figure—due to either death or divorce—shapes a girl's romantic relationships later in life. Using a descriptive case study approach, researchers conducted in-depth interviews with three women who all experienced being left by their fathers during childhood.Through these conversations, several recurring themes emerged, shedding light on the long-lasting emotional effects of growing up without a dad. The five key themes identified were: emotional dependence, a deep need for protection and acceptance, impulsive decisions around marriage, insecurity in relationships, and a tendency to seek a father figure in romantic partners. What’s striking is that none of the participants described any positive or healthy impact this early loss had on their adult relationships. Instead, the absence of a father left a significant emotional gap, influencing how they connect with and trust men. The study highlights just how vital a present, loving, and supportive father figure is in a girl's life. A healthy father-daughter relationship helps shape a girl's expectations of men, teaches her how to build strong emotional bonds, and plays a crucial role in how she navigates love and intimacy as an adult.